STUDI KASUS PESERTA DIDIK YANG MENDAPATKAN HASIL BELAJAR RENDAH DI KELAS X MAN 2 PONTIANAK - Reckha Mamta Yusli Ananda; Purwanti Purwanti; Yuline Yuline (Universitas Tanjungpura, 2019)
AbstractThe focus of this study is students who get low learning outcomes in class X MAN 2 Pontianak. The research method is descriptive, a form of case study research. The case subjects were two people. The counseling model for case I subjects is the REBT counseling model with behavioral dispute techniques. The results after being given alternative assistance experienced positive changes, especially in improving learning outcomes, especially in Arabic language lessons, getting an even UAS score of 82. The counseling model used in case 2 subjects was Behavioral, with systematic disentization techniques and assertive practice. The results obtained have shown changes in learning by increasing learning outcomes in Arabic language lessons, which scored 82 when the UAS was even Keywords: Case Study, Low Learning Outcomes